Characteristics of tolerance to stress of future specialists with socionomy occupations - Halyna Dubchak (Social Welfare: Interdisciplinary Approach, 2015)
The article discusses the issue of tolerance to stress of future specialists with socionomy occupations. The "professional stress" concept is expanded. The empirical research of stress tolerance of modern Ukrainian students from universities and vocational schools is described. General and distinctive characteristics of tolerance to stress of future specialists with different socionomy occupations are determined